Exercise-Induced Extracellular Vesicles Delay the Progression of Prostate Cancer - Sadovska, Lilite; Auders, Jānis; Keiša, Laura; Romanchikova, Nadezhda; Silamiķele, Laila; Kreišmane, Madara; Zayakin, Pawel; Takahashi, Satoru; Kalniņa, Zane; Linē, Aija (Frontiers in Molecular Biosciences, 2022)
Increasing evidence suggests that regular physical exercise not only reduces the risk of cancer but also improves functional capacity, treatment efficacy and disease outcome in cancer patients. At least partially, these effects are mediated by the secretome of the tissues responding to exercise. The secreted molecules can be released in a carrier-free form or enclosed into extracellular vesicles (EVs). Several recent studies have shown that EVs are actively released into the circulation during physical exercise. Here, we for the first time investigated the effects of exercise-induced EVs on the progression of cancer in an F344 rat model of metastatic prostate cancer. Although we did not observe a consistent increase in the circulating EV levels, RNA sequencing analysis demonstrated substantial changes in the RNA content of EVs collected before and immediately after forced wheel running exercise as well as differences between EVs from runners at resting state and sedentary rats. The major RNA biotype in EVs was mRNA, followed by miRNA and rRNA. Molecular functions of differentially expressed RNAs reflected various physiological processes including protein folding, metabolism and regulation of immune responses triggered by the exercise in the parental cells. Intravenous administration of exercise-induced EVs into F344 rats with orthotopically injected syngeneic prostate cancer cells PLS10, demonstrated reduction of the primary tumor volume by 35% and possibly – attenuation of lung metastases. Hence, our data provide the first evidence that exercise-induced EVs may modulate tumor physiology and delay the progression of cancer.